O'nyong nyong virus molecular determinants of unique vector specificity reside in non-structural protein 3. - Kali D Saxton-Shaw; Jeremy P Ledermann; Erin M Borland; Janae L Stovall; Eric C Mossel; Amber J Singh; Jeffrey Wilusz; Ann M Powers (Public Library of Science (PLoS), 2013)
O'nyong nyong virus (ONNV) and Chikungunya virus (CHIKV) are two closely related alphaviruses with very different infection patterns in the mosquito, Anopheles gambiae. ONNV is the only alphavirus transmitted by anopheline mosquitoes, but specific molecular determinants of infection of this unique vector specificity remain unidentified. Fifteen distinct chimeric viruses were constructed to evaluate both structural and non-structural regions of the genome and infection patterns were determined through artificial infectious feeds in An. gambiae with each of these chimeras. Only one region, non-structural protein 3 (nsP3), was sufficient to up-regulate infection to rates similar to those seen with parental ONNV. When ONNV non-structural protein 3 (nsP3) replaced nsP3 from CHIKV virus in one of the chimeric viruses, infection rates in An. gambiae went from 0% to 63.5%. No other single gene or viral region addition was able to restore infection rates. Thus, we have shown that a non-structural genome element involved in viral replication is a major element involved in ONNV's unique vector specificity.